2003
DOI: 10.1002/ana.10751
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging shows delayed ischemic striatal neurodegeneration

Abstract: Brief focal ischemia leading to temporary neurological deficits induces delayed hyperintensity on T1-weighted magnetic resonance imaging (MRI) in the striatum of humans and rats. The T1 hyperintensity may stem from biochemical alterations including manganese (Mn) accumulation after ischemia. To clarify the significance of this MRI modification, we investigated the changes in the dorsolateral striatum of rats from 4 hours through 16 weeks after a 15-minute period of middle cerebral artery occlusion (MCAO), for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
138
4

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(153 citation statements)
references
References 69 publications
11
138
4
Order By: Relevance
“…Even though morphologically similar to those of Fujioka et al (2003), the subcortical lesions described in our study had a different appearance on follow-up MRI. Since it involved the same brain structure, region-specific differences in lesion evolution are not a plausible explanation for this difference.…”
Section: Lesion Type-dependent Relaxation Time Changes: Pathophysiolocontrasting
confidence: 43%
See 1 more Smart Citation
“…Even though morphologically similar to those of Fujioka et al (2003), the subcortical lesions described in our study had a different appearance on follow-up MRI. Since it involved the same brain structure, region-specific differences in lesion evolution are not a plausible explanation for this difference.…”
Section: Lesion Type-dependent Relaxation Time Changes: Pathophysiolocontrasting
confidence: 43%
“…In mild transient ischemia of 30 mins and less, MRI changes have been shown to take a different course (Fujioka et al, 2003; van Lookeren Campagne et al, 1999). After a 15-mins vascular occlusion, Fujioka et al (2003) showed a delayed hyperintensity on T 1 -w images that was accompanied by a hypointensity on T 2 -w images between 5 days and 16 weeks after MCAO. These relaxation time changes were attributed to manganese accumulation in the striatum in concert with neurodegeneration and an inflammatory response that led to delayed impairment in cognitive function.…”
Section: Ischemia Duration-dependent Relaxation Time Changesmentioning
confidence: 99%
“…These changes affected the caudoputamen and cortex, appeared around 1 week after the stroke and disappeared in the following weeks to months together with progressive tissue atrophy ( Figure 3A). These authors subsequently reported 59 six additional clinical cases who, despite full neurological recovery, showed a decline in global cognitive functions at 12 months of follow-up. They replicated these MR findings in two experimental studies in Wistar rats subjected to 15-minute proximal MCAo, 35,59 where a striatal T2W hypointense signal appeared at day 5 to 7 but was preceded by transient hyperintensity at day 1, indicating vasogenic edema, whereas the T1W hyperintensity peaked at B4 weeks and then subsided slowly over months ( Figure 3B).…”
Section: Animal Modelsmentioning
confidence: 99%
“…These authors subsequently reported 59 six additional clinical cases who, despite full neurological recovery, showed a decline in global cognitive functions at 12 months of follow-up. They replicated these MR findings in two experimental studies in Wistar rats subjected to 15-minute proximal MCAo, 35,59 where a striatal T2W hypointense signal appeared at day 5 to 7 but was preceded by transient hyperintensity at day 1, indicating vasogenic edema, whereas the T1W hyperintensity peaked at B4 weeks and then subsided slowly over months ( Figure 3B). Histology showed a severe and progressive SNL affecting the striatum, evolving from a mean of B20% of surviving neurons at 4 hours and day 3 down to only 3% at 16 weeks, together with marked and sustained astrocytosis and MA, yet not fulfilling criteria for pannecrosis.…”
Section: Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation